Experimental investigation of an innovative biomass-fired micro-ORC system for cogeneration applications. (December 2020) - Carraro, Gianluca; Bori, Viola; Lazzaretto, Andrea; Toniato, Giuseppe; Danieli, Piero
Abstract: In the transition towards smart grid systems, a problem of increasing importance is the distributed generation of thermal and electric power at low cost and low environmental impact. This work proposes an innovative cogeneration system based on a biomass boiler and a micro-Organic Rankine Cycle (ORC) unit, suitable for application in isolated micro grids. The goal of this study is twofold: i) the analysis of the design choices that were made to achieve a good compromise between efficiency and cheapness of the micro-cogeneration system, and ii) the performance evaluation of the system for variations of key parameters, such as temperature and flow rate of the thermal oil, mass flow rate of the cooling water and operating assets of the ORC unit. Results of the in-depth experimental campaign show that 2250 rpm for the pump and 2300 rpm for the expander are the best combination of speeds to achieve the highest performance. They allow obtaining the maximum values of the ORC electric efficiency (7.3%), energy utilization factor of the cogeneration system (62%) and of the ORC unit (93%). With an oil temperature of about 150 °C, the achieved power production is 2530 W and the efficiency of the expander is 57%. Highlights: The performance of a biomass-fired ORC system has been experimentally evaluated. The design choices to build a market-ready micro-cogeneration unit are presented. Key parameters are varied to assess their effect on the operation of the system. The maximum net electric power and efficiency are 2.2 kW and 7.3%, respectively.